STRATEGI PEMANFAATAN MEDIA INSTAGRAM SEBAGAI MEDIA PEMASARAN PADA AKUN @MBUN.ID - Danti Kusuma Ningrum; Anugrah Indah Safitri; Syakira Minnatia Mumtaza; Gushuana Gushuana; Amanda Aurely (Media Riset Bisnis Manajemen Akuntansi, 2026)
This research aims to examine the strategy of utilizing the Instagram application as a culinary promotion medium on the account @mbun.id. The background of this study is based on the advancement of digital technology as a marketing media, especially Instagram, which holds great potential for product marketing. The objectives of this research are to expand market reach, increase interaction with consumers, and effectively drive sales because technology enables advanced features that support digital marketing goals. The method used in this study is qualitative research with data collection techniques through observation such as content marketing, search engine optimization (SEO), social media marketing, and data-driven strategies. The results show an increase in sales due to the use of Instagram as a marketing media. From this study, it is concluded that the Instagram application plays an important role in expanding market reach and increasing sales.Keywords : Aplikasi, Instagram, Pemasaran, Teknologi